1987
DOI: 10.1254/jjp.43.445
|View full text |Cite
|
Sign up to set email alerts
|

A trial for kinetic evaluation of the antagonistic potency of several .BETA.-antagonists on presynaptic .BETA.-adrenoceptors.

Abstract: Abstract-The antagonistic potency, pA2, of several non-selective i3-antagonists on presynaptic (3-adrenoceptors was evaluated using a parallel line assay and MacKay's equation against isoproterenol-induced increases in 3H release in isolated guinea-pig pulmonary arteries preloaded with 3H-norepinephrine. Cumulatively applied isoproterenol at 10-9 M, 10-8 M and 10-7 M dose-dependently increased 3H release evoked by transmural field stimulation at 1 Hz . 19-Antagonists tested dose-dependently antagonized the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…As an agonist, carteolol is nearly as potent (i.e., has similar EC 50 values) on the β 3 -receptor (5 µM; Table 1) as it has on β 1 /β 2 -receptors (0.2-3 µM) (Takayanagi et al 1989;Koike et al 1996) and is in all cases only a partial agonist (intrinsic activity 40-60%). However, as an antagonist, carteolol has a very high affinity for β 1 /β 2 -receptors (≤ 1 nM) (Kuwahara et al 1987;Takayanagi et al 1989;Koike et al 1996) but, as shown here, has very low affinity (> 10 µM) for β 3 -receptors. Thus, carteolol antagonist or agonist selectivity is close to unity for β 3 -receptors, in contrast with the ≈1000-fold ratio for β 1 /β 2 -receptors.…”
Section: Antagonist Properties Of Carteololsupporting
confidence: 52%
See 1 more Smart Citation
“…As an agonist, carteolol is nearly as potent (i.e., has similar EC 50 values) on the β 3 -receptor (5 µM; Table 1) as it has on β 1 /β 2 -receptors (0.2-3 µM) (Takayanagi et al 1989;Koike et al 1996) and is in all cases only a partial agonist (intrinsic activity 40-60%). However, as an antagonist, carteolol has a very high affinity for β 1 /β 2 -receptors (≤ 1 nM) (Kuwahara et al 1987;Takayanagi et al 1989;Koike et al 1996) but, as shown here, has very low affinity (> 10 µM) for β 3 -receptors. Thus, carteolol antagonist or agonist selectivity is close to unity for β 3 -receptors, in contrast with the ≈1000-fold ratio for β 1 /β 2 -receptors.…”
Section: Antagonist Properties Of Carteololsupporting
confidence: 52%
“…The calculated pK B values for carteolol as an antagonist were 4.6 against norepinephrine, 5.0 against BRL-37344, and 4.8 against CGP-12177; i.e., carteolol is a comparatively weak antagonist on the β 3 -receptor with a pK B ≤ 5 (which is a lower affinity than, for instance, propranolol has on these receptors). This value should be compared with the affinity of carteolol as an antagonist at the β 1 /β 2 -receptor, which is four to six orders of magnitude better (pA 2 of 9-11) (Kuwahara et al 1987;Takayanagi et al 1989;Koike et al 1996).…”
Section: Antagonist Properties Of Carteololmentioning
confidence: 99%
“…We observed that 10-6 M nadolol and phentolamine can produce about a 250 fold blockade of effects of exogenous isoprenaline on guinea-pig right atria (data not shown). Additionally, the antagonistic potency, pA2, of nadolol against effects of isoprenaline has been reported to be 9.78 ± 0.05 (Kuwahara et al, 1987). Thus, this concentration of nadolol and phentolamine (10-6 M) should be high enough to antagonize adequately the effects of NA adrenoceptors.…”
Section: Discussionmentioning
confidence: 97%